Failure to find a distance effect in pigeon choice: Manipulating amount and delay of reinforcement. Issue 3 (8th October 2020) - Sanabria, Federico; Bell, Matthew C.
Abstract : The choice behavior of primates, including humans, displays a distance effect: Latency to choose between alternatives appears to increase with smaller differences in value. There is, so far, no demonstration of this effect in birds. Tests of distance effects in birds have been conducted in binary choice situations with a dominant alternative, where one alternative is superior to the other in all aspects that meaningfully contribute to value (e.g., provides access to the same reinforcer, but with a shorter delay). The present study considers the possibility that including dominant alternatives in choice tests precludes distance effects. Four pigeons were presented with binary choices between alternatives that varied in amount and delay. Some choices had a dominant alternative (smaller–sooner or larger–later vs. smaller–later) and some did not (smaller–sooner vs. larger–later). Across phases, only the delay to the smaller–sooner reinforcer varied. Distance effects were expected to be expressed as longer latencies as choice between smaller–sooner and larger–later reinforcers approached indifference. Despite the sensitivity of choice to differences in amount and delay, no distance effect was observed. Alternative explanations for the failure to find a distance effect in pigeon choice, including the Sequential Choice Model (SCM), are discussed.